ATTITUDES TOWARDS THE INVESTIGATION OF ROTATING OBSTETRICS INMATES IN A LIMA-PERU HOSPITAL - Barja Ore, John (2019)
Objective: Determine attitudes towards the investigation of rotating obstetrics inmates at Sergio E. Bernales Hospital (HSEB) during December 2018 to January 2019. Methods: Transversal study. The population was made up of obstetrics interns who performed professional practices to whom a validated scale of 28 items distributed in 6 dimensions was applied, which assessed attitudes towards research. Results: 57 obstetrics interns participated in the study. The average age was 23.5 ± 2.1 years and 96.5% were female. 54.4% of inmates presented a regular attitude towards scientific research, 24.6% had a good attitude and 21% had a bad attitude. 93.0% of inmates agreed or strongly agreed that publication in a journal helps improve clinical practice, most felt able to interpret a scientific article (68.4%) and prepared to conduct research career related (54.3%); On the other hand, they considered that in order to carry out quality research in the university they had to have basic physical and virtual tools (94.7%) and that the scientific writing course should focus on teaching the preparation of an article (84.2 %). The majority disagreed and disagreed in opting for another graduation modality other than the thesis (50.9%). Conclusion: More than half of HSEB's obstetric inmates had a regular attitude toward research. The results show the need to continue strengthening and promoting research in obstetrics students.